2023
DOI: 10.3390/foods12193706
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Pivotal Roles of Probiotics, Their Components, and Metabolites in Preventing Colon Cancer

Xue Deng,
Jing Yang,
Yu Zhang
et al.

Abstract: Diet, lifestyle, and gut microbiota composition are key risk factors for the progression of colon cancer. Probiotics are living microorganisms that can offer health benefits to the parasitifer when ingested in competent quantities. Several in vivo, in vitro, and clinical studies have demonstrated that probiotics can prevent and mitigate the development of colon cancer. The anti-colon cancer mechanisms of probiotics include the suppression of cell proliferation and the promotion of cancer cell apoptosis, immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…The omega-3 polyunsaturated fatty acid eicosapentaenoic acid (EPA) inhibits the development of HCC induced by DEN and HFD, suggesting that EPA attenuates the development of obesity-related MASLD-HCC by suppressing STAT3 (Inoue-Yamauchi et al, 2018). An increasing number of studies have shown that probiotics can prevent and mitigate the development of cancer (Deng et al, 2023;Zhao et al, 2023). Probiotics suppressed HCC pathogenesis by inhibiting the gene expression of pro-inflammatory cytokines and reducing oxidative stress in a hepatocyte-specific PTEN knockout mouse MASLD model (Arai et al, 2022).…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…The omega-3 polyunsaturated fatty acid eicosapentaenoic acid (EPA) inhibits the development of HCC induced by DEN and HFD, suggesting that EPA attenuates the development of obesity-related MASLD-HCC by suppressing STAT3 (Inoue-Yamauchi et al, 2018). An increasing number of studies have shown that probiotics can prevent and mitigate the development of cancer (Deng et al, 2023;Zhao et al, 2023). Probiotics suppressed HCC pathogenesis by inhibiting the gene expression of pro-inflammatory cytokines and reducing oxidative stress in a hepatocyte-specific PTEN knockout mouse MASLD model (Arai et al, 2022).…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…In recent years, the incidence rate of colon cancer in China has been rising rapidly and this trend is predicted to continue in the next few years [ 2 ]. The occurrence and development of colon cancer is a complicated process influenced by multiple factors like genetic factors, environment, and lifestyle; however, most cases of colon cancer can be due to lifestyle and aging, while a few cases are attributed to underlying genetic diseases [ 3 ]. In addition, research over the past few decades has shown that the role of the intestinal microbiota is becoming more and more important in health and disease, and the occurrence of various diseases is related to biological dysbiosis in the gut [ 4 ].…”
Section: Introductionmentioning
confidence: 99%